Smart Innovation: The Key to MSME Competitiveness in the Digital Era - Miranda, Mira (Riviera Publishing, 2024)
This research examines innovation in the digital era as a new step in the competition among Micro, Small, and Medium Enterprises (MSMEs). The method used is quantitative, employing a questionnaire distributed to 10 respondents, coupled with data analysis via validity tests, reliability tests, and statistical tests. The validity test results indicate that most questionnaire items are valid with an average correlation value of 0.46, while the reliability test using Cronbach's Alpha yields a score of 0.85, signifying that this instrument is dependable. Descriptive statistical analysis and Chi-Square tests reveal a significant relationship between the use of digital platforms and sales improvement, with a Chi-Square value of 14.25 and a p-value of 0.03. These findings suggest that the more intensively MSMEs use e-commerce, the greater their chances of increasing revenue. Smart innovation through the adoption of digital technology, especially e-commerce, proves important in strengthening MSME competitiveness. This research recommends the need for support from the government and relevant institutions in the form of training and access to financing to facilitate the digital transformation of MSME players. With these steps, it is hoped that MSMEs can not only compete more effectively in local markets but also contribute to national economic growth.